Implementing Project-Based Learning (PBL) Model in Malay Culture’s lecture at Universitas Tuanku Tambusai Kampar-Riau - Nurmalina Nurmalina (Universitas Pahlawan Tuanku Tambusai, 2020)
Learning model is one of the most critical factors in learning. To enhance the learning creativity and master the learning competency is, therefore, to promote the implementation of PBL by means of associating between the technology and the Malay cultural community. By promoting PBL, the students’ activeness and creativity is significantly increasing.In this model, the teacher purely acts as a facilitator and evaluator of the student’s worksand or products presented in the results of the project. By producing real works, the students are motivated to increasingly enhance their learning activeness and creativity. The purpose of conducting this study was to determine the effectiveness of the implementation of PBL learning model in UniversitasPahlawanTuankuTambusai Riau in efforts to increase the students’creativity in the Malay Culture’ subject matter. In conclusion, the implementation of the PBL learning model in Malay Culture’ subject matter can significantly enhance the students’activeness and creativity.